Mediating effects of organizational culture on the relationship between organizational context and organizational performance / Mohammed Abdullah Ali Alkhawlani - Alkhawlani, Mohammed Abdullah Ali (2016)
This research examine the construct relationships between organizational structure, strategy, and the congruence between structure and strategy in terms of organizational context, and their effect on organizational performance, then examine the effect of organizational culture as a mediator between these relationships. A total of 216 of Yemen airways non-managerial employees from four main departments participate in the study. The main objective of the study was to examine the significant of organizational culture as a plausible mediator between the congruence of organizational structure, and strategy and organizational performance and then between organizational structure, strategy and organizational performance. The findings stated that an organizational culture significantly and partially mediate the relationship between organizational context and organizational performance. Similarly, organizational culture significantly and partially mediates the relationship between organizational structure and organizational strategy. Other objective is to identify the effect of organizational context on organizational performance and organizational culture. The findings reported that organizational context is positively effects on organizational performance and organizational culture. Then the next objective is to determine the effect of organizational culture on organizational performance, and the finding is organizational culture has a significant correlation with the organizational performance. Last objective is to identify the effect of organizational structure and organizational strategy on organizational performance and organizational culture. In this objective the research findings stated that organizational strategy has a positive effect on organizational culture and organizational performance. Meanwhile, it's found that there is no significance relationship between organizational structure and organizational performance but it has a significance effect on the organizational culture. This study reported that organizational culture served as a significant mediator for the relationship between organizational structure and organizational performance. Organizational culture was also found to be a significant mediator for the relationship between organizational strategy and organizational performance, and the more important is that the plausible significant effect of organizational culture as a mediator between the congruence of organizational structure and strategy, show a higher correlation and effect on the organizational performance better than the effect of structure and strategy separately. Furthermore, this research shaped in ten hypothesis to analyze an organizational context structural model (congruent of structure and strategy) as an independent variable, organizational culture as a mediator and organizational performance as a dependent variable. The results indicate that 48 percent of the variance explains organizational performance was accounted for by the dimension of organizational context as a congruent factor. However, only 20 percent of the variance explained organizational culture was accounted by dimensions in organizational context and then organizational structure explained 34 percent of organizational culture while an organizational strategy explains 22 percent of organizational culture. Moreover, the variance percentage explain an organizational performance where 11 and 12 respectively. Finally, theoretical, practical, and methodological contributions as well as recommendations for future research were discussed.